Tunable Bulk Polymer Planar Bragg Gratings Electrified via Femtosecond Laser Reductive Sintering of CuO Nanoparticles - Kefer, Stefan; Bischoff, Kay; Roth, Gian Luca; Haubner, Julian; Schmauß, Bernhard; Hellmann, Ralf (Advanced Optical Materials, 2021)
This contribution demonstrates and discusses electrically tunable polymer planar Bragg gratings based on bulk cyclic olefin copolymers. A lithographic single-writing-step method and femtosecond laser reductive sintering of copper(II) oxide nanoparticles are subsequently employed in order to generate buried photonic structures and copper conducting paths on top of the polymer substrate. This way, the necessary number of process steps for fabricating a planar polymer-based electro-optical device is greatly reduced. The response of a fully electrified grating structure follows temperature changes, induced by the copper conducting path, with sensitivities up to −31 pm K−1. Dilatometric measurements show that the specimen's behavior is correlated to the situationally reduced thermal expansion of the bulk polymer substrate. In consequence, the tuning response of the photonic platform follows a second order polynomial, whereas a direct current of 30 mA, which correlates to a power consumption of 18.3 mW, leads to a local temperature increase and a residual Bragg wavelength shift of 19.6 K and −547 pm, respectively. Moreover, the outstanding flexibility of the proposed fabrication concept is underlined by demonstrating alternative conducting path geometries, whereas one of the additional designs is adapted to control the spectral width of the Bragg grating's reflection peak.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Bragg gratings; CuO nanoparticles; cyclic olefin copolymers; electro-optic tuning; integrated photonics; laser reductive sintering